Monitoring of 220Rn Concentrations in Buildings of Kufa Technical Institute, Iraq - Ali Abid Abojassim Al-Hamidawi (Science and Technology of Nuclear Installations)
This paper presents the measurements of thoron and the progeny in fifteen buildings in Kufa Technical Institute, Iraq, from June 2015 to April 2015 using RAD-7 detectors. Also, annual effective dose rate was calculated in all buildings under study. The thoron concentration varies from 05.35±0.58 Bq/m3 to 53.50±1.82 Bq/m3 with an average 18.39±4.18 Bq/m3. The concentration of thoron daughters was found to vary from 0.14 mWL to 1.44 mWL with an average 0.53±0.11 mWL. The annual effective doses due to thoron mainly vary from 0.042 mSv/y to 0.81 mSv/y with an average 0.20±0.06 mSv/y. The preliminary results in this study indicate that they may be suitable for evaluating the indoor 220Rn and its progeny concentrations whenever the public exposure to 220Rn and its progeny is taken into account. During this survey, the continuous difficulty in measuring thoron was also pointed out, due to its short half-life and faults in the measuring system.